Huashi Runzao decoction for primary Sjögren disease: a double-blind, randomized controlled trial combined with m6A and m5C RNA modification analysis - Huang, Ziwei; Deng, Tiantian; Zhang, Xiya; Lei, Chunxin; Zhang, Yan; Yang, Jianying; He, Qian; Liao, Jiahe; Chen, Jiaqi; Yang, Liwen; Gu, Xiaofeng; Luo, Jing; et al. (Frontiers in Pharmacology, 2025)
BackgroundHuashi Runzao decoction (HRD), a Chinese herbal formula, has been used in clinical practice for patients with primary Sjögren disease (pSD) for years. However, the benefits of HRD for pSD have not been evaluated, and HRD epigenetic mechanism of action remains unexplored.ObjectivesWe conducted a double-blind, randomized, placebo-controlled clinical trial to evaluate the efficacy and safety of HRD in patients with pSD and to explore its epigenetic mechanism of action.MethodsThe clinical scores (including oral dryness, dry eye, dryness, fatigue, and limb pain visual analogue scales scores and the ESSPRI) of pSD patients were recorded at baseline and every 4 weeks thereafter. The disease activity scores (including the ESSDAI and ClinESSDAI), exocrine gland function variables (including the result of Schirmer’s test and salivary flow rate), serological indices (ESR, CRP, IgG, IgA, and IgM) and short-form-36 health survey (SF-36) score were evaluated at baseline and 12 weeks later. Peripheral blood samples were collected from patients and healthy volunteers to determine RNA methylation (m6A and m5C) levels and analyse regulatory factor expression.ResultsHRD improved exocrine gland function in pSD patients and increased saliva (P = 0.049) and tear (P = 0.005) secretion. It also improved patients’ perceptions of subjective symptoms, including oral dryness (P < 0.001), dry eye (P = 0.004), dryness (P = 0.001), and limb pain (P = 0.008) and yielded greater ESSPRIs (P = 0.001), reduced patients’ disease activity according to the ClinESSDAI (P = 0.038) and improved their quality of life. Moreover, HRD increased m6A levels and decreased m5C levels in pSD patients, and HNRNPA2B1 was identified as a potential key epigenetic regulator.ConclusionHRD, a Chinese herbal medicine, may be a promising treatment for pSD, especially for glandular damage. The therapeutic effects of this decoction may be achieved by alteration of the HNRNPA2B1 gene, altering m6A and m5C levels in pSD patients.